Dietary Iron Deficiency Impaired Peripheral Immunity but Did Not Alter Brain Microglia in PRRSV-Infected Neonatal Piglets - Leyshon, Brian J.; Ji, Peng; Caputo, Megan P.; Matt, Stephanie M.; Johnson, Rodney W. (Frontiers in Immunology, 2019)
During the postnatal period the developing brain is vulnerable to insults including nutrient insufficiency and infection that may lead to disrupted development and cognitive dysfunction. Since iron deficiency (ID) often presents with immunodeficiency, the objective of this study was to investigate peripheral viremia and inflammation as well as brain microglial phenotype and function when ID and respiratory infection occur simultaneously in a neonatal piglet model. On postnatal day 2 (PD 2) male and female piglets were assigned to one of four treatments and fed either control or ID milk replacer. On PD 8 half the pigs on each diet were inoculated with either vehicle or porcine reproductive and respiratory syndrome virus (PRRSV; P-129). Blood samples were collected prior to inoculation (PD 7) and repeated once weekly. Rectal temperature, feeding score and sickness behavior were measured daily until PD 28. Hematocrit, hemoglobin, and serum iron were reduced by ID but not PRRSV infection. PRRSV-infected piglets displayed viremia by PD 14; however, those fed control diet had lower viral titer on PD 28, while circulating virus remained elevated in those fed an ID diet, suggesting that ID either impaired immune function necessary for viral clearance or increased viral replication. ID piglets infected with PRRSV displayed reduced sickness behavior compared to those fed control diet on PD 13-15 and 18-20. While ID piglet sickness behavior progressively worsened, piglets fed control diet displayed improved sickness score after PD 21. Microglia isolated from PRRSV piglets had increased MHCII expression and phagocytic activity ex vivo compared to uninfected piglets. ID did not alter microglial activation or phagocytic activity. Similarly, microglial cytokine expression was increased by PRRSV but unaffected by ID, in stark contrast to peripheral blood mononuclear cell (PBMC) cytokine expression, which was increased by infection and generally decreased by ID. Taken together, these data suggest that ID decreases peripheral immune function leading to increased viremia, but immune activity in the brain is protected from acute ID.